Romeo and Juliet by Nureyev, music by Prokofiev - Prokofiev, Sergey 1891-1953 (Bel Air Média, 1995)
Experience Rudolf Nureyev's sumptuous landmark 1995 production of Prokofiev's Romeo and Juliet at the Opéra Bastille, starring Monique Loudières as Juliet, Manuel Legris as Romeo, Charles Jude as Tybalt, and Lionel Delanoë as Mercutio. I'm convinced that Renaissance Verona and Elizabethan London, in a society divided between old superstitions and a hunger for the new world, had sex and violence in common; which, oddly enough, links them to our times. - Rudolf Nureyev Nureyev's 1995 Romeo and Juliet was one of the legendary artist's last productions for the Paris Opera Ballet. He had performed the role of Romeo himself in Kenneth MacMillan's 1965 version, and later mounted his own productions in 1977, 1980, 1983, and 1984. Framed by fresco-inspired sets and costumes that bring Renaissance Verona to life, his 1995 production places particular emphasis on Tybalt and Mercutio, and the quarrelsome people of Verona, setting them in an atmosphere as superb in appearance as it is cruel in reality. The star-studded production was directed by Alexandre Tarta, with choreography and staging by Nureyev, sets by Ezio Frigerio, and costumes by Ezio Frigerio and Mauro Pagano. The Nureyev-handpicked leads--Monique Loudières, Manuel Legris, Charles Jude, and Lionel Delanoë--were joined by the Corps de Ballet de l'Opéra national de Paris, and the Orchestre de l'Opéra national de Paris under the direction of Vello Pähn
Keywords: Ballets; Webcast; Filmed ballets; Internet videos; Vidéos sur Internet; Ballets filmés